Indian Lavender [Bursera penicillata (D.C.) Engl.] - a Review - Somappa, K.; Uppin, S. F. (Indian Forester, 1979)
Bursera is an aromatic essential oil plant introduced into India by two private enterprising Scotsman - P. J. Anderson and G. N. Hamphries in 1912 at Thatgunni estate near Bangalore, Karnataka State. Forest department has started it's cultivation since 1958. The genus Bursera has n=12 number of chromosome. Plants are dioecious and known to regenerate both by artificial and natural means as well as by sexual and asexual methods, cuttings being the commercial method. It grows well on lateristic red soils and prefers arid tropical climate with temperature variation between 18 ° C and 35 ° C and rainfall between 450mm and 650mm annually. The climatic conditions around Bangalore are found to be very much condusive to grow this species on a large scale. The cuttings are planted in 0.5m cube pits dug at 6 × 6m interval. A fertilizer dose of 40-80:20-40gm of Ammonium sulphate, Superphosphate and muriate of potash per plant per year could be applied to have vigorous growth. Being a deciduous species tree remains leafless from November to March and new flush starts during April-May with simultaneous flowering. Trees starts bearing 3 to 4 years after planting. No serious pests and diseases have been reported except for Pestalotia helerocornis fungus which causes die-back for which the control measure is spray of 0.2% Emulcicop. Harvesting is done either by picking of berries or by collecting the fallen berries during August. The oil is distilled by usual steam distillation of air dried husks which yield 10 to 14% of oil. About 25kg of oil can be expected from one hectare plantation. Trees attain maximum bearing 13 years after planting, when the yield of oil is expected to fetch Rs. 6000/- per hectare